Trabalho docente na educação infantil: entre a precarização e valorização profissional - Bertonceli, Mariane (2016)
his dissertation is the result of study on the increase or precarious professor of child education work in the municipality of Salto do Lontra / PR, in the course of 2014 and 2015. We analyze the teacher's work in the current situation, considering the work category as a central element, and the sub-categories that relate the conditions of teaching in kindergarten, specific object of this dissertation. Selected subcategories are: teacher training, teacher compensation, material and human conditions of work and the pedagogical aspect, matters intrinsically crucial to the appreciation or teacher's career precariousness that works with young children. The current situation of the municipality and analyzed problems are treated from the materialist method and therefore are analyzed historically and dialectically, not as isolated incidents, but in the whole panorama. The qualitative research consisted of theoretical and empirical basis. The instruments used to collect data were semi-structured interviews, questionnaires, documentary research and observation. We perform the data comparison with other local realities that present advances in relation to aspects analyzed in the supply of EI Salto do Lontra. Thus, this study constitutes an invitation to any and all teachers, especially those dedicated to the hard work with small children, a call to fight for their recognition as workers and also the importance of early childhood education that has historically delegated to a lesser role in the educational plan.